The Influence of International price Adaptation on Overseas Sales Volume. Case Study on PT Indofood Sukses Makmur Tbk - Melda Dea Safitri; Nurul Aini; Agung Augustrianto; Nasihatun Falah; Tari Fitrianti; Siti Indriani (Dinasti Publisher, 2026)
This research entitled The Effect of International Price Adaptation on Foreign Sales Volume seeks to examine the relationship and impact of pricing strategies about sales performing in global markets. The study is based on the importance of pricing strategies in international competition. A quantitative approach was used with a sample of 39 export-oriented business actors. Data were analyzed using validity, reliability, normality, correlation, regression, F-test, and t-test. The outcomes indicate that all instruments are valid and highly dependable with a 0.944 Cronbach's Alpha score, and the information is distributed normally with a importance value of 0.071. Regression analysis shows a positive effect with the equation Y = 15.092 + 0.653X. The F-test and t-test results confirm a significant influence with a significance level of 0.001. Thus, it may be said that appropriate price adaptation strategies can improve competitiveness and increase sales volume in international markets.